Carbon Sequestration Potential of Paddy Soil in China under the Carbon Peaking and Carbon Neutrality Goals - Longlong Bai; Yaqi Sheng; Lili Xu; Xiang Gao; Yongxin Zhang; Jinsong Deng (中国工程科学)
The paddy ecosystem, as a unique soil ecosystem formed by artificial cultivation, holds great potentials for carbon sequestration, which is crucial for realizing the carbon peaking and carbon neutrality ("dual carbon") goals in the agricultural sector of China. This study constructs 5995 simulation units using the rice planting area information acquired through remote sensing in China in 2021. Subsequently, it uses a denitrification-decomposition (DNDC) model to simulate the spatial distribution of surface soil organic carbon (SOC) density in fields in China from 2021 to 2040, and predicts the future trend of the SOC. Results of the study indicate that the paddy soil in China exhibits a carbon sink under the current planting conditions. The average carbon storage of the surface paddy soil (0~20 cm) in China was 4.10 Pg C in 2021 and will be 4.32 Pg C in 2030 and 4.49 Pg C in 2040; the carbon storage will increase year by year. The carbon sequestration potential of paddy soil in China will be 22 Tg C‧a-1 during 2021—2030 and 17 Tg C‧a-1 during 2030—2040; the average annual growth rate will slow down, and the carbon sequestration potential of soil will gradually reach saturation. In the next two decades, the SOC density of paddy fields in most regions of China will change, and the increased areas will be significantly greater than the decreased areas, with a maximum growth rate of 9.2% and a maximum decrease rate of 8.0%. Scenario simulations indicate that straw returning and fertilizer application could significantly increase the carbon storage in paddy soils. These findings hold scientific significance and practical values in fully utilizing the carbon sink function of paddy soils, reducing greenhouse gas emissions, and advancing the "dual carbon" goals in the agricultural sector.